1984
DOI: 10.1021/bi00306a031
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of cholera toxin with gangliosides: differential effects of the oligosaccharide of ganglioside GM1 and of micellar gangliosides

Abstract: Ultraviolet difference absorption spectra of cholera toxin and its B protomer produced by the oligosaccharide moiety of the monosialoganglioside GM1 were measured as a function of the oligosaccharide concentration. In the presence of oligosaccharide, the spectrum is characterized by three peaks at 282, 288, and 292 nm. A linear increase in difference absorption was observed at these wavelengths vs. oligosaccharide concentration; a saturation effect occurred when the molar ratio of oligosaccharide to cholera to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…A quantitative analysis of the spectra allowed us to estimate that no greater than 3-4% change in @-sheet or a-helix content could Occur in the presence of the receptor. Previous fluorescence and absorption spectroscopy titration experiments with oligo-GMl (Fishman et al, 1978;Tomasi et al, 1984), as well as the estimated toxinreceptor binding constants (Sattler et al, 1977(Sattler et al, , 1978Fishman et al, 1978), strongly indicate that under the experimental conditions of this study (receptor to B subunit monomer molar ratio of 2: 1) virtually all the protein present in solution is associated with the receptor. The absence of unbound protein in our samples of subunit B mixtures with ganglioside GMl or oligo-GM, is further corroborated by the studies of temperature dependence of infrared spectra (Figures 2 and 3), which demonstrate a complete elimination of a thermotropic transition characteristic of the free protein.…”
Section: Discussionsupporting
confidence: 68%
“…A quantitative analysis of the spectra allowed us to estimate that no greater than 3-4% change in @-sheet or a-helix content could Occur in the presence of the receptor. Previous fluorescence and absorption spectroscopy titration experiments with oligo-GMl (Fishman et al, 1978;Tomasi et al, 1984), as well as the estimated toxinreceptor binding constants (Sattler et al, 1977(Sattler et al, , 1978Fishman et al, 1978), strongly indicate that under the experimental conditions of this study (receptor to B subunit monomer molar ratio of 2: 1) virtually all the protein present in solution is associated with the receptor. The absence of unbound protein in our samples of subunit B mixtures with ganglioside GMl or oligo-GM, is further corroborated by the studies of temperature dependence of infrared spectra (Figures 2 and 3), which demonstrate a complete elimination of a thermotropic transition characteristic of the free protein.…”
Section: Discussionsupporting
confidence: 68%
“…The calorimetric results presented in this paper revealed that the major effect of ganglioside is on the cooperative interactions between the B subunits and demonstrate further that there is little, if any, direct interaction between the A subunit and ganglioside GMl. This conformational difference probably does not represent a gross structural rearrangement (Dwyer & Bloomfield, 1982) but rather local amino acid side chain reorientation due to ganglioside GMi association (Tomasi et al, 1984). The binding site for the ganglioside GMl has been postulated as being at the interface between B subunit monomers (DeWolf et al, 1981), thus providing a structural basis for the observed enhancement in intersubunit interactions.…”
Section: Discussionmentioning
confidence: 98%
“…By contrast, incubation of intact toxin with ganglioside GMl results in only a slight increase in the transition temperature for the A subunit transition. The results from several spectroscopic investigations (Fishman et al, 1978;Sillerud et al, 1981;Tomasi et al, 1984) have suggested the existence of a conformational change in the B subunit upon binding to ganglioside GMl. The calorimetric results presented in this paper revealed that the major effect of ganglioside is on the cooperative interactions between the B subunits and demonstrate further that there is little, if any, direct interaction between the A subunit and ganglioside GMl.…”
Section: Discussionmentioning
confidence: 99%
“…This would result in the dissociation of CT into CT A and CT B and subsequent penetration of the A component into the cell membrane. The initial highly specific interaction of CT with the oligosaccharide moiety of GM, (oligo-GM,) appears to occur without any substantial conformational change (De Wolf et al, 1981b;Tomasi et al, 1984). It was shown (De Wolf et al, 1981a,b;Sillerud et al, 1981;Tomasi et al, 1984;Ludwig et al, 1985) that the lone Trp-88 residue of each /3-polypeptide chain is an important determinant in this interaction.…”
mentioning
confidence: 99%
“…The initial highly specific interaction of CT with the oligosaccharide moiety of GM, (oligo-GM,) appears to occur without any substantial conformational change (De Wolf et al, 1981b;Tomasi et al, 1984). It was shown (De Wolf et al, 1981a,b;Sillerud et al, 1981;Tomasi et al, 1984;Ludwig et al, 1985) that the lone Trp-88 residue of each /3-polypeptide chain is an important determinant in this interaction. In a previous paper (De Wolf et al, 1985), the pH dependence of the fluorescence characteristics of CT that are related to this lone Trp-88 were examined.…”
mentioning
confidence: 99%